2019
DOI: 10.1186/s40942-019-0183-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of intravitreal bevacizumab for ischemic central retinal vein occlusion

Abstract: Background Although previous studies have evaluated the effect of anti-VEGF therapies for central retinal vein occlusion (CRVO) patients, the majority of previous studies have excluded or included a very small number of patients with ischemic CRVO (iCRVO). The aim of our study is to examine the effects of bevacizumab on macular edema secondary to ischemic central retinal vein occlusion, as well as the effects on central choroidal thickness and best-corrected visual acuity. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In another study by Leangelo Hall et al, 12 the baseline BCVA was Log MAR 1.3 and CMT as 858 ± 311 microns comparable to the findings in ischaemic CRVO in our study.…”
Section: Discussionsupporting
confidence: 91%
“…In another study by Leangelo Hall et al, 12 the baseline BCVA was Log MAR 1.3 and CMT as 858 ± 311 microns comparable to the findings in ischaemic CRVO in our study.…”
Section: Discussionsupporting
confidence: 91%
“…06, Jun 2022 303 edema. 15,16 There was a significant level of (P < 0.01) correlation between the mean change in CMT of all study stages and the mean change in BCVA. One month after each injection, BCVA improved significantly, as a result of reduced macular edema and vascular leakage.…”
Section: Discussionmentioning
confidence: 80%
“…Hall et al . [ 22 ] found no visual gains in ischemic CRVO despite giving anti-VEGF for six months. In RAVE, 50% of patients developed neovascular complications, despite intensive anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These studies concluded that anti-VEGF in ischemic CRVO can decrease macular edema but cannot prevent neovascular complications. [ 21 22 ]…”
Section: Discussionmentioning
confidence: 99%